전통 및 수정 중요도-성과도 분석을 통한 어린이집 사용자와 건축 전문가의 공간 별 리스크 인식 비교 분석 - 이경태; 김홍주; 제갈재웅; 김재원; 김주형; Lee, Kyung-Tae; Kim, Hong-Ju; Jekal, Jae-Woong; Kim, Jae-Won; Kim, Ju-Hyung (한국건설관리학회 논문집, 23(1), 2022)
Daycare center is an important space for children's mental, physical and social development. Each space of daycare center should be designed and constructed considering interests of end-users such as children and teachers. However, insufficient related guidelines and standardized design and construction of daycare center to moderate potential risks of each space. This arises from the difference in perception of each space between end-users (head and sub teachers) and construction experts (designers and contractors). Therefore, research framework was developed for analyzing the factors of perception differences of each space in daycare center between these groups applied traditional and modified Importance-Performance Analysis (IPA). By comparing risk perception between end-users and experts in two methods, it can be support as construction guide for daycare center in the future and will help minimize conflicts in construction among stakeholders. Moreover, it was found that traditional IPA is comfortable to catch prior project perception of participants, and revised IPA is considered to judge outputs by identifying participant's importance based on the satisfaction of the project performance. Therefore, if IPAs are applied according to the characteristics of the circumstances, it is possible to analyze the perception difference between end-users and construction experts based on the context before and after the construction of the daycare center. 어린이집은 아이들의 심신 및 사회성 발달 등이 이루어지는 중요한 공간이다. 따라서 어린이집 각 공간은 사용자인 아이뿐 아니라 교사의 특성을 고려하여 맞춤형 설계 및 시공이 이루어져야 한다. 그러나 불충분한 관련 법규 및 획일화된 설계 시공 과정은 어린이집 각 공간의 특성을 살리지 못하고 있는 실정이다. 이는 최종사용자(원장, 교사) 및 건설 전문가(설계 및 시공자) 사이의 각 공간별 중요도-성과도 인식차이에서 발생한다. 이에 본 연구에서는 각 공간 및 집단 간 인식차이 요인 분석을 위한 프레임워크를 개발하고 전통 및 수정 IPA를 통해 어린이집 건설 시 우선 고려되어야 할 요인들을 도출하였다. 이를 토대로 두 집단의 인식을 비교하고, 분석방법에 다른 결과를 비교함으로, 향후 어린이집 발주 시 활용 가능하며 시공 및 운영 과정에서 각자의 공간에 대한 인식을 파악하여 갈등 발생 최소화에 도움이 될 것이다. 또한, 각 IPA 방법에 따라 전통 IPA가 사전의 인식을 보는데 수월하다면, 수정 IPA는 성과물의 만족도를 기준으로 중요도를 파악함으로 결과물에 대한 판단이 가능할 것으로 여겨진다. 따라서 IPA의 특성에 따라서 결과를 비교한다면, 어린이집 건설 전후 상황에 따른 사용자와 건설 전문가 집단의 인식차이 분석이 가능할 것이다.